Pastagens de capim-elefante, consorciadas com azevém, espécies de crescimento espontâneo e trevo branco ou amendoim forrageiro, manejadas com bovinos leiteiros - Ziech, Magnos Fernando (2007)
The elephantgrass (EG) use a grazing in primarily based in the conventional strategy, established in singular form. Informations and researchs about its use on mixed pastures system are scarce. Then, the objetive of this work was to evaluate the dynamic, nutritive value and behavior of lactating cows in two pasture-based systems (PS), with EG + ryegrass (RG) + white clover (WC) + spontaneous growing species (SGS) for PS1; and EG + RG + forage peanut (FP) + SGS for PS2. Four paddocks, each one with 0,25ha, were used in the avaliation. The EG was established in lines with a distance of 4m among each one of them. Pastures was fertilized with 50-40-40kg/ha of N-P-K, respectively. Nine grazings were performed during the experimental period (326 days in PS1 and 336 in PS2). Holstein cows receiving 3.5kg/daily complementary concentrate feed were used in the evaluation. Pregraze samples were taken that represented average paddock herbage mass. The initial forage mass, the botanical composition and the structural components of EG were evaluated. Samples from hand-plucking method were collected to analyze neutral detergent fiber (NDF), crude protein (CP), in vitro dry matter digestibility (IVDMD), in vitro organic matter digestibility (IVOMD) and total digestibility nutrients (TDN). In the winter period, evaluations were taken in three grazing cycles of ingestive behavior cows. The time of elephantgrass (EG) grazing, species established in space between lines grazing, total grazing (EG + species established in space between lines grazing), rumination and idle were the behavioral parameters observed. Considering the mean data of experimentation, the results of forage mass, legumes and stocking rate were similar among the evaluated systems. The better results of nutritive value had been found in the forage system mixed with WC. The means time of between lines grazing were superior in the PS1. The rumination and ildle time didn't show statistical difference among treatments. The results show that the EG can be used under the systematic proposed.